(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The goal of this study is to highlight the issues that female inmates face when they areincarcerated. And disclose all of the rights that are safeguarded for and by women convicts, as well as thecircumstances that lead women to commit crimes. Women encounter the same issues in jail systems thatwere predominantly created by and for males, notwithstanding cultural and resource inequalities. Theseinclude sexual assault, inadequate medical care, child loss, marital violence, and other forms of physicaland mental abuse. The issue only emerges when a poor, uneducated woman joins a jail and is frequentlyphysically and verbally mistreated by prison employees. Under several particular provisions for the care,welfare, and development of women and children, the Indian Constitution gives equal rights to women aswell as rights to prisoners and those who have been arrested. The main problems that affect womenconvicts and their dependent children in the jail, and to collect information and suggestions on howthese problems could be effectively handled.